Validation of LRINEC (Laboratory Risk Indicators for Diagnosis of Necrotizing Fasciitis) Scoring System for the Diagnosis of Necrotizing Fasciitis (Journal of Surgical Sciences, 2020)
Background : Necrotizing fasciitis (NF) is a rare but potentially fatal infection involving the subcutaneous tissue and fascia. Different classifications and terminology has been used in NF based on affected anatomy, microbial cause and depth of infection. Clinical scores like the laboratory risk indicators for NF (LRINEC) scores are available to help diagnose NF and differentiate it from other skin and soft tissue infections.Methods : A total of 100 patients were included in the study between January 2014 to June 2014. This prospective study was done on patients admitted in surgery department of DMCH with symptoms suggestive of soft tissue infections during the study period.Results : Mean age was found 46.5(±13.8) years in severe cellulitis and 50.9(±9.8) years in necroting fasciitis (p>0.05). Male were predominant (60%). 80% of NF had DM. The validation test for LRINEC score e”6 vs necrotizing fasciitis had sensitivity of 66%, specificity 84%, accuracy 75%, positive and negative predictive values were 80.49% and 71.19% respectively. Mortality of NF was 6%.Conclusion : The LRINEC score is an impressive diagnostic tool to distinguish necrotizing fasciitis from other severe soft tissue infections, but it is not useful for early recognition of necrotizing fasciitis.Journal of Surgical Sciences (2019) Vol. 23(2): 75-80